Molecular diversity by olefin cross-metathesis on solid support. Generation of libraries of biologically promising β-lactam derivatives - Mendez, Luciana (2018)
The application of the reagent-based diversification strategy for generation of libraries of biologically promising β-lactam derivatives is described. Key features are the versatility of the linker used and the cross-metathesis functionalization at the cleavage step. From an immobilized primary library, diversity was expanded by applying different cleavage conditions, leading to a series of cholesterol absorption inhibitor analogues together with interesting hybrid compounds through incorporation of a chalcone moiety.